Effect of Arthrospira platensis (Spirulina) as a dietary supplement during transition period in dairy buffaloes - Giuseppe De Rosa; Vittoria L. Barile; Carmela M.A. Barone; Claudia Lambiase; Francesco Serrapica; Giovanna De Matteis; Emanuela Rossi; Corrado Pacelli (Revista Científica)
It is widely recognized that in mammals, the period just before and immediately after calving, until the peak’s lactation, is a stressful period impairing animal performance and immune response. Some studies have proposed the use of Arthrospira platensis (Spirulina), a natural immunostimulant, as a dietary supplement in cows and sheep to improve the antioxidant response. To date, no similar research has been reported on the buffalo species. Therefore, we investigated the effect of Spirulina on body condition score (BCS), yield and quality of milk, and oxidative stress response through the assessment of reactive oxygen metabolites (d-ROMs test) and the biological antioxidant potential (BAP test) of twenty-four Italian Mediterranean buffaloes. The animals were equally divided into two groups (control=C and Spirulina=S) fed with the same total mixed ration. In top dressing mode, the S group additionally received 50 g/head/d of freeze-dried Spirulina for one month before calving and 100 g/head/d for 90 d after calving. Milk production was recorded daily on the farm’s computer system, and milk composition (protein, fat, and lactose) was determined at 30, 60, and 90 d after calving using Milkoscan (Foss, Denmark). BCS was determined at group formation and 30, 60, and 90 days after calving. Colostrum was collected within 6-8 hours post-calving, and its immunoglobulin content was immediately measured by an optical refractometer (Brix degrees). d-ROMs and BAP were measured on serum blood samples taken at group formation, at calving, 15 and 90 d after calving. Data were analyzed by a two-way analysis of variance using treatment, time of sampling, and relative interaction as factors. Where appropriate, the Tukey post hoc test was used to identify significant differences between means. For all variables, the interaction was not significant. Spirulina supplementation did not influence yield, milk quality, BCS, or colostrum quality. Group S showed a significantly higher mean BAP value (U-Carr) than the control (2730.17 vs. 2511.28, p<0.05) and a lower level of d-ROMs (54.15 vs. 78.45, p<0.05), indicating a better antioxidant response to oxidative stress. As expected, the sampling time significantly affected both BAP and d-ROMs (p<0.001), with the highest BAP value at 90 d and the lowest d-ROMs at 30 d before calving. We conclude that Spirulina supplementation during the transition period.